Stakeholders' perceptions on the community-based forest management projects implementation in selected areas of Leyte Province, Philippines - Bautista, Eugenia N. (Sylvatrop, 2012)
The study aimed to evaluate the extent of implementation and level of people’s participation in four selected sites of Community-Based Forest Management (CBFM) projects in the province of Leyte, Philippines. Findings will serve as basis for proposed interventions toward the improvement of program implementation. The extent of implementation of the CBFM projects in terms of the rules and regulations under the Implementation Stage was perceived by the primary stakeholders or project beneficiaries as substantially implemented in the projects managed by CUFA-MPC, FSMIRAI and Mag-aso CBRMPSA, whereas fully implemented by PIAFDAI. Significant differences were established in the perception of the primary stakeholders in the extent of implementation of the rules and regulations among project sites. The perception of PIAFDAI project beneficiaries is significantly higher compared to CUFA-MPC, FSMIRAI and Mag-aso CBRMPSA. The secondary stakeholders, i.e., DENR implementers, LGUs and other assisting organizations perceived the extent of implementation of the rules and regulations in the CBFM projects managed by PIAFDAI, CUFA-MPC and FSMIRAI as substantially implemented whereas in the Mag-aso CBRMPSA it is perceived as partially implemented. The project beneficiaries perceived their level of participation in key CBFM activities as moderate by PIAFDAI and CUFA-MPC and low participation by the FSMIRAI and Mag-aso CBRMPSA beneficiaries. Highly significant differences were established on the primary stakeholders’ perception on their level of participation in activities, namely, application of silvicultural practices such as thinning, weeding, and assisted natural regeneration, plantation establishment, maintenance and protection in established plantations, livelihood activities, and forest product utilization. Participation or involvement of the four POs in CBFM key activities is not significantly related with age, gender, civil status, educational attainment, monthly income, household size and religion except for the gender of FSMIRAI members which is highly significant. The study drew some recommendations to improve the CBFM implementation which included the need for a strong coordination among CBFM primary (project beneficiaries) and secondary (DENR implementers, LGUs and other assisting organizations) stakeholders in all CBFM activities, the requirement for teamwork and concerted efforts of these stakeholders to ensure effective implementation and strengthen project beneficiaries’ participation, and creation of an effective and always functional participatory monitoring and evaluation team composed of representatives from the DENR, POs, LGUs and other assisting organizations.